Sistema de Tutoría Inteligente (Intelligent Tutoring System) para la Enseñanza de Ecuaciones de Primer Grado Dirigida a Estudiantes de Octavo y Noveno de Básica Superior Usando CTAT - Cuenca Camacho, Carlos Andres (2024)
Currently, intelligent tutoring systems (ITS) and artificial intelligence (AI) play a fundamental role in education by providing personalized instruction. These systems evaluate errors, offer educational resources, and track the student's progress continuously. In line with these initiatives, this Master's Thesis (MT) aims to develop an ITS for teaching first-degree equations considering the student's learning style (LS). To address the object of study, an ITS for teaching first-degree equations was built in three phases: In the first phase, research and analysis of previous work related to IT focused on education was conducted. The objective was to know the types of architectures used in these systems, as well as a review of the most efficient authoring tools for the development of ITS; following the guidelines proposed in each research method applied; including active observation, review, and follow-up, case study, and the Barbara Kitchenham methodology. In the second phase, the modules of the ITS were built according to the tri modular architecture and the authoring tool elected in the previous phase. In the third phase, an evaluation of the system in an educational environment was carried out through an experimental plan and tests on 13 students from eighth and ninth grade of basic secondary school belonging to the Technical School Zumbi, who were selected by applying non-probabilistic quota sampling, checking the ease of use and the acceptance of the system; as a result, a level of acceptance of 53.8% "Very high" and an ease of use of 46.2% as "Easy" were obtained, values that are shared between the metrics applied. To implement the application in a Web environment, technologies such as React, Next, and MongoDB were used, which were selected after a previous analysis in search of a scalable and high-performance system. Finally, the MT identifies that the ITS provides significant support to students in their teaching process, taking into account the LS to track the student's progress, promoting a more personalized, motivating, and student-centered learning. Keywords: intelligent tutoring systems (ITS), artificial intelligence (AI), personalized learning, educational resources